Comparative Proteome Profiling of Saliva Between Estrus and Non-Estrus Stages by Employing Label-Free Quantitation (LFQ) and Tandem Mass Tag (TMT)-LC-MS/MS Analysis: An Approach for Estrus Biomarker Identification in Bubalus bubalis - Singh, Laishram Kipjen; Pandey, Mamta; Baithalu, Rubina Kumari; Fernandes, Abhijeet; Ali, Syed Azmal; Jaiswal, Latika; Pannu, Suryaprakash; Neeraj,; Mohanty, Tushar K.; Kumaresan, A.; Datta, Tirtha K.; Kumar, Sudarshan; et al. (Frontiers in Genetics, 2022)
Accurate determination of estrus is essentially required for efficient reproduction management of farm animals. Buffalo is a shy breeder and doesn’t manifest overt estrus signs that make estrus detection difficult, resulting in a poor conception rate. Therefore, identifying estrus biomarkers in easily accessible biofluid-like saliva is of utmost interest. In the current study, we generated saliva proteome profiles during the proestrus (PE), estrus (E), metestrus (ME), and diestrus (DE) stages of the buffalo estrous cycle using both label-free (LFQ) and labeled (TMT) quantitation and mass spectrometry analysis. A total of 520 proteins were identified as DEPs in LFQ, and among these, 59 and 04 proteins were upregulated (FC≥1.5) and downregulated (FC≤0.5) during the E vs. PE, ME, and DE comparisons, respectively. Similarly, TMT-LC-MS/MS analysis identified 369 DEPs, among these, 74 and 73 proteins were upregulated and downregulated during E vs. PE, ME, and DE stages, respectively. Functional annotations of GO terms showed enrichment of glycolysis, pyruvate metabolism, endopeptidase inhibitor activity, salivary secretion, innate immune response, calcium ion binding, oocyte meiosis, and estrogen signaling. Over-expression of, SERPINB1, HSPA1A, VMO1, SDF4, LCN1, OBP, and ENO3 proteins during estrus was further confirmed by western blotting. This is the first comprehensive report on differential proteome analysis of buffalo saliva between estrus and non-estrus stages. This study generated an important panel of candidate proteins that may be considered buffalo estrus biomarkers and which can be applied in the development of a diagnostic kit for estrus detection in buffalo.